2014
DOI: 10.1021/ja502806r
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoroethanethiol: An Additive for Efficient One-Pot Peptide Ligation−Desulfurization Chemistry

Abstract: Native chemical ligation followed by desulfurization is a powerful strategy for the assembly of proteins. Here we describe the development of a high-yielding, one-pot ligation-desulfurization protocol that uses trifluoroethanethiol (TFET) as a novel thiol additive. The synthetic utility of this TFET-enabled methodology is demonstrated by the efficient multi-step one-pot syntheses of two tick-derived proteins, chimadanin and madanin-1, without the need for any intermediary purification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
125
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 48 publications
0
125
0
7
Order By: Relevance
“…Very recently, the application of the β-thiol Asp derivative 97 [122] has been reported in the one-pot, three-component total synthesis of madanin-1 123 (Scheme 30), a small, Cys-free thrombin inhibitory protein derived from the hard tick H. longicornis [124]. In this study, the target 60-amino acid protein 123 was disconnected at Asp and Ala ligation junctions using ligation-desulfurization chemistry mediated by β-thiol Asp and Cys, respectively.…”
Section: Aspartic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, the application of the β-thiol Asp derivative 97 [122] has been reported in the one-pot, three-component total synthesis of madanin-1 123 (Scheme 30), a small, Cys-free thrombin inhibitory protein derived from the hard tick H. longicornis [124]. In this study, the target 60-amino acid protein 123 was disconnected at Asp and Ala ligation junctions using ligation-desulfurization chemistry mediated by β-thiol Asp and Cys, respectively.…”
Section: Aspartic Acidmentioning
confidence: 99%
“…In this study, the target 60-amino acid protein 123 was disconnected at Asp and Ala ligation junctions using ligation-desulfurization chemistry mediated by β-thiol Asp and Cys, respectively. Interestingly, for the construction of the target protein, the authors also reported the use of a novel thiol additive, trifluoroethanethiol (TFET) 124, which facilitates the facile application of a one-pot ligation-desulfurization protocol [124]. Previous attempts to streamline the ligation-desulfurization strategy into a one-pot process have been hampered by the use of aryl thiol ligation additives which, because of their radical quenching ability [125], complicate the radical desulfurization process [126][127][128].…”
Section: Aspartic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus aimed for employing ligation conditions which allow one-pot free-radical desulfurization. 16 Initial attempts with the native chemical ligation (NCL) catalyst trifluoroethanethiol (TFET) 17 resulted in large amounts of thioester hydrolysis of the branched peptide 1. We thus opted for methyl thioglycolate (MTG) as a thiol additive, 18 which resulted in slower ligation kinetics but which showed drastically reduced hydrolysis product formation, while still allowing one-pot desulfurization.…”
mentioning
confidence: 99%
“…Molecular weight characterization of all polymers synthesized in this study were carried out using both size exclusion chromatography (Scheme 2B and 2C and Supporting Information) and MALDI-TOF mass spectrometry (see Supplementary Table 1 Polymers 11-13 bearing pseudo-cysteine end groups were next assessed as substrates for NCL reactions with model peptide thioester Ac-LYRANG-S(CH2)2CO2Et 14 (synthesized by Fmoc-SPPS, see Supplementary Information) to generate end-functionalized polymer-peptide conjugates. All NCL reactions were conducted at pH 7.0 using tris-carboxyethylphosphine (TCEP) as a reductant and trifluoroethane thiol (TFET) 30 as an additive to convert the unreactive S-propionate ethyl ester of 14 into the corresponding reactive S-trifluoroethyl ester to accelerate the rate of the reactions (Table 1). We initially assessed the efficiency of NCL reactions between pseudo-cysteine end-functionalized polymer 11 and peptide thioester 14 in a number of different buffer/solvent mixtures.…”
mentioning
confidence: 99%